Cyber Security Analysis of Academic Services based on Domain Delivery Services and Support using Indonesian E-Government Ratings (PEGI) - Riadi, Imam; Riyadi Yanto, Iwan Tti; Handoyo, Eko (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2020)
Safe academic services are the most important part of universities. The security of academic services is very important to maintain information optimally and safely. Along with the development of technology, academic information services are often misused by some irresponsible parties that can cause threats. To prevent these things from happening, it is necessary to know the extent of governance of higher education academic information system security by evaluating. So the research was conducted to determine the maturity of the security of Higher Education academic information service security by using the COBIT 5 framework in the DSS05 domain. The DSS05 domain in COBIT 5 is a good framework for use in implementing and evaluating the security of academic information services. Meanwhile, to determine the achievement of the evaluation of the security level of academic information systems, the Indonesian e-government ranking (PEGI) method is required. The combination of the COBIT 5 framework in the DSS05 domain using the PEGI method in academic information security service is able to provide a level of achievement in the form of Customer Value. The results of the COBIT 5 framework analysis of the DSS05 domain using the PEGI method get a score of 3.50 so that the quality of academic information service security evaluation achievement is at a very good level. At this level, universities are increasingly open to technological development. Higher education has applied the concept of quantification in every process, and has always been monitored and controlled for its performance in the security of academic information systems.